PENERAPAN PRINSIF KESEHATAN DAN KESELAMATAN KERJA DI UKM PANDE BESI TRADISIONAL - Sunardi, Sunardi; Zendrato, Rosleini Ria Putri (Lembaga Penelitian dan Pengabdian Masyarakat, 2020)
AbstractPartners in the Community Partnership Program activities are Pande Besi PRASOJO located in Nangsri Kidul RT 2 / IV Nangsri Kebakkramat Karanganyar and Pande Besi MANDIRI located at Â Dondong RT 2/IX Klumprit Mojolaban Sukoharjo. The two partners are traditional blacksmiths. The problems faced by the two partners are relatively the same, namely: 1) traditional / conventional production processes; 2) do not apply the principles of Occupational Health & Safety. Solutions that will be carried out from this activity are: 1) production of blower and grinding tools; 2) the use of personal protective equipment (PPE). The method that will be carried out to realize the objectives of the PKM implementation program is through: 1) Procurement of electric blowers and grinders for both partners; 2) Increased knowledge and training in the use of personal protective equipment (PPE). In this method both partner SMEs are involved in each activity starting from problem identification, action analysis, action planning and implementation of activities. Through this method, the identified problems and actions to be taken are bottom up proposals. So that every action that will be carried out is right on target and is able to realize the objectives to be achieved maximally. The results of the Community Partnership Program activities were Pande Besi PRASOJO and Pande Besi MANDIRI succeeded in increasing the quantity and quality of products through the procurement of blower and grinding tools. Both partners have also implemented occupational health and safety principles through increased knowledge and use of PPE.